2021
DOI: 10.1002/1878-0261.12901
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cell profiling for precision oncology

Abstract: Analysis of circulating tumor cells (CTCs) collected from patient's blood offers a broad range of opportunities in the field of precision oncology. With new advances in profiling technology, it is now possible to demonstrate an association between the molecular profiles of CTCs and tumor response to therapy. In this Review, we discuss mechanisms of tumor resistance to therapy and their link to phenotypic and genotypic properties of CTCs. We summarize key technologies used to isolate and analyze CTCs and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 177 publications
(198 reference statements)
0
35
0
Order By: Relevance
“…As so far, the CellSearch platform, a CTCs detection method based on immunological assay with the epithelial cell adhesion molecule (EpCAM), is the only one to date that is approved by FDA for CTC detection in metastatic breast cancer, prostate cancer, and colorectal cancer. 38 In our study, it was the most common method for CTC enumeration in SCLC. We observed that except for pooled data analysis of the association between post-therapy CTCs detected by CellSearch and PFS, higher CTCs count (baseline and after treatment) was significantly correlated with shorter OS/PFS in SCLC.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As so far, the CellSearch platform, a CTCs detection method based on immunological assay with the epithelial cell adhesion molecule (EpCAM), is the only one to date that is approved by FDA for CTC detection in metastatic breast cancer, prostate cancer, and colorectal cancer. 38 In our study, it was the most common method for CTC enumeration in SCLC. We observed that except for pooled data analysis of the association between post-therapy CTCs detected by CellSearch and PFS, higher CTCs count (baseline and after treatment) was significantly correlated with shorter OS/PFS in SCLC.…”
Section: Discussionmentioning
confidence: 82%
“… 1 , 7 Unlike conventional tissue biopsy, CTCs detection is a non-invasive test that can provide a “moving picture” of longitudinal tumor progression and obtain a comprehensive understanding of the heterogeneous tumor cells throughout the body. 8 , 38 As mentioned before, although numerous studies have indicated that higher CTCs levels were correlated with worse prognosis and early disease recurrence among the vast majority of solid tumors, the prognostic value of CTCs in SCLC remains controversial. It could be attributed to the fact that different detection methods, different sampling times, and unstandardized cut-off values were used in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, by preserving the molecular identity of the main tumor, they allow a range of analyses including DNA, RNA, and protein levels, as well as functional ones. Moreover, they can surrogate the current methods of follow-up of CRC (with images) leading to earlier diagnosis of recurrences and reduce costs [ 27 ].…”
Section: Liquid Biopsy (Lb) and Targeted Approaches For Analysismentioning
confidence: 99%
“…This special issue on current challenges of liquid biopsy research includes seven articles written by experts in this field of research and covers multiple facets of liquid biopsy: a. CTCs -Vasseur et al [30] summarize the evidence that has established CTCs as an independent prognostic factor in several cancer types (clinical validity), in both localized and metastatic settings, with a particular focus on breast cancer, and the published or ongoing phase II-III clinical trials designed to demonstrate the clinical utility of CTCs. Moreover, Labib et al [31] review key technologies used to isolate and analyze CTCs and discuss recent clinical studies that examined CTCs for genomic and proteomic predictors of responsiveness to therapy. Finally, current limitations that still hamper the implementation of CTCs into clinical practice are pointed out.…”
mentioning
confidence: 99%